De la musique avant toute chose - Tabachnik, Michel; Debray, Régis (Paris Buchet-Chastel, 2008)
In 'De la musique avant toute chose', Tabachnik offers readers his “ideal concert”. It consists of works by Richard Strauss, Béla Bartok, Igor Stravinsky, Xenakis and Boulez. Of the last two, he talks about their personalities, the meaning of their musical research and their friendship for him. He also recounts how he became close to a sacred monster of orchestral conducting, Herbert Von Karajan, whose exacting standards and exemplary commitment to his art he underlines.But this book is more than an album of remarkably vivid memories. Tabachnik is a musician who reflects on his art. He seeks to respond to the ‘call of being’, inspired by the painter Kandinsky. Régis Debray's ‘letter to Michel’, by way of preface, deftly places us in the position of a ‘willing ignoramus’. It opens up a dialogue that Tabachnik is eager to share. It helps to make this book an introduction to contemporary music, which is still so little loved, so little understood. (Translated with DeepL.com)
Keywords: Music philosophy and esthetics